Association between genetic polymorphism of telomere-associated gene ACYP2 and the risk of HAPE among the Chinese Han population: A Case–control study. Issue 13 (March 2017) - Zhu, Linhao; Liu, Lijun; He, Xue; Yan, Mengdan; Du, Jieli; Yang, Hua; Zhang, Yuan; Yuan, Dongya; Jin, Tianbo
Abstract : Abstract: High-altitude pulmonary edema (HAPE) is a hypoxia-induced, life-threatening, pulmonary edema, which is characterized by exaggerated pulmonary hypertension caused by stress failure. ACYP2 was found to associated with telomere length, the aim of this study was to identify whether ACYP2 polymorphisms increase or decrease HAPE risk in the Chinese Han individuals. In present study, we have genotyped 7 single-nucleotide polymorphisms (SNPs) in ACYP2 to determine the haplotypes in a case–control study with 265 HAPE patients and 303 healthy individuals. Genotypes were determined using the Sequenom MassARRAY method. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by unconditional logistic regression with adjustment for gender and age. We found 3 SNPs yielded significant evidence for association with HAPE risk which had not been investigated before. Rs6713088 was found to have a 1.85- and 1.30-fold increased risk of HAPE in the recessive and additive model. The GT of rs843752 also conferred an increased risk of HAPE (GT/TT: OR = 1.51, 95% CI: 1.05–2.16, P = 0.026) and the genotype frequency distributions of rs843752 had significant difference between cases and controls. The CC genotype of rs17045754 had a protect effect on HAPE patients, and it was found to have a 0.29-fold reduced risk of HAPE in the recessive model. Although additional, larger population-based studies are needed to confirm these findings, our study shed light on the association between ACYP2 variant and HAPE risk in Han Chinese population for the first time.